PERTUMBUHAN EKONOMI KELUARGA DI KAMPUNG KB KELURAHAN AIR DINGIN KECAMATAN BUKIT RAYA KOTA PEKANBARU - Mustaqim, Mustaqim; Sumardi, Sumardi; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the economic growth of families in KB Village Air Dingin Village, Bukit Raya City, Pekanbaru. The sample in this study amounted to 20 people, namely residents in KB Village with Simple Random Sampling technique. Data collection techniques using a questionnaire. Data analysis techniques using the SPSS program and percentage calculation. The results of this study indicate that the Family Economic Growth in KB Village in Air Dingin Village, Bukit Raya District, Pekanbaru City is high.Key Words: Family Economic Growth in KB Village, Air Dingin Subdistrict, Bukit Raya City, Pekanbaru City.